Positive Psychology and Gratitude Interventions: A Randomized Clinical Trial - Cunha, Lúzie Fofonka; Pellanda, Lucia Campos; Reppold, Caroline Tozzi (Frontiers in Psychology, 2019)
Objective: the purpose of this study was to assess the effect of a gratitude intervention on a community sample of adults in relation to aspects involving well-being and mental health. Method: A randomized clinical trial was conducted with 1,337 participants, composed of an intervention group (Gratitude group, n= 446) and two control groups (Hassles group, n= 444 and Neutral Events group, n= 447). Participants assigned to the intervention condition were asked to write daily gratitude lists for 14 days, listing moments they had been grateful for during the day. The outcomes analyzed were affect, depression, happiness and life satisfaction. Participants completed the Positive Affect and Negative Affect Schedule (PANAS), Center for Epidemiological Studies Depression Scale (CES-D), Subjective Happiness Scale (SHS) and Satisfaction with Life Scale (SWLS) three times: pre- and post-intervention and at 14 days after the end of the intervention. Due to attrition, the number of participants analyzed was 410. Results: Before the intervention, the groups did not differ in any of the variables examined, and loss to follow-up was random among the three groups. The gratitude intervention managed to increase positive affect, subjective happiness and life satisfaction, and reduce negative affect and depression symptoms. This change was greater than the changes in the control groups in relation to positive affect. In the other outcomes analyzed, similar changes were observed in the gratitude intervention and the neutral events intervention. Conclusions: Some similarities were found between the Gratitude and the Neutral Events groups probably because participants in the last group usually recorded positive events from their days on the lists, turning it into an activity very similar to that proposed to the gratitude group. Some limitations of the study are discussed, such as the high dropout rate for self-performed online interventions. It is necessary to investigate which characteristics of an intervention ensure better results when the intervention is performed online. Trial Registration: The study is registered in the Brazilian Clinical Trials Registry, under No. RBR-9j9myd. Trial URL: http://www.ensaiosclinicos.gov.br/rg/RBR-9j9myd/